Binge drinking and sexual risk behavior among US sexual and gender minority college students. Issue 1 (15th December 2021) - Li, Jason J.; Hyun, Sunah; Stevens, Courtney; Chen, Justin A.; Liu, Cindy H.
Abstract: Background and Objectives: Binge drinking and sexual risk behaviors have historically been associated with lesbian, gay, bisexual, and transgender (LGBT) adults; however, few studies have described this association among broader sexual and gender minority (SGM) students, who often identify outside of LGBT (e.g., asexual, queer). This study examined the relationship between binge drinking and sexual risk behaviors among SGM versus non‐SGM college students. Methods: A retrospective analysis was conducted with cross‐sectional data from the Spring 2017 American College Health Association‐National College Health Assessment (ACHA‐NCHA) survey among US undergraduates ( n = 47, 821) across 92 institutions. Binge drinking was measured as more than five drinks consumed the last time the student socialized; sexual risk behavior was measured as the number of sexual partners in the past 12 months. Results: Numerous undergraduates nationally identify as SGM (19.9%), with bisexual (32.7%), other SGM (26.1%), and asexual (25.4%) students comprising the largest subgroups. Prevalent among both SGM (28.1%) and non‐SGM (29.6%) students, binge drinking had a significant main effect on the number of sexual partners. A significant interaction effect was observed between SGM identity and binge drinking on the number of sexual partners, such that this association was stronger in SGM versus non‐SGM students. This effect remained significant across multiple SGM subgroups. Discussion and Conclusions: SGM students are more prevalent and diverse than previously reported. While prevalent overall, binge drinking may be uniquely sexualized among SGM students. Scientific Significance: In the first large‐scale study assessing drinking among disaggregated SGM college students, data suggest tailoring alcohol interventions to SGM students, particularly those identifying outside of LGBT.